Komposisi Kimia Pasir Pantai di Selatan Kulon Progo dan Implikasi terhadap Provenance - Irzon, Ronaldo (Pusat Survei Geologi, 2018)
Abstrak - Coastal sediment geochemical characters can be utilized in tracing the source material and linkage with other rock units in a region. This study is intended to determine the geochemistry composition of the beach sands in four location on the south coast of Kulon Progo, Yogyakarta Special Province. The geochemical content was than used to characterize the coastal sediments, establish the relationship of the sample, and trace the source material. Geochemistry content of surface sample in comparison to subsurface sample on three selected locations are discussed. XRF and ICP-MS were used to measure the major oxides, trace and rare earth elements composition of the selected samples. The beach sands of these four locations is inferred derived from the same source based on bivariate plots of major oxides versus SiO2, degrees of elements coefficient correlation, and the trends on REE spider diagram. Rb, Sr, Zr, U, dan Th are more concentrated in the surface samples whilst magnetic materials in the subsurface ones. The selected coastal sediments are chemically immature and formed under arid condition. Source material is considered relatively fresh and ranges from mafic to felsic character. The Andesite intrusion around Ijo Mountain is thought to be more appropriate as a source material based on that character compared to other rock units as well as the results of Mount Merapi activities reinforced by chemical index of alteration calculations, oxide ratios and rare earth composition.Keyword : beach sands, the Andesite, geochemistry, provenance.